Strengthening and Repair of a Precast Reinforced Concrete Residential Building - M. Jamal Shannag; Mahmoud Higazey (Salehan Institute of Higher Education, 2020)
The deterioration or ageing of the existing infrastructures coupled with increased safety requirements necessitate immediate strengthening. Developing long lasting and cost effective repair techniques and materials continue to capture the attention of concrete professionals worldwide. The main purpose of this investigation was to extend the life span of a multi-storey precast reinforced concrete structure built in Riyadh 40 years ago. The condition assessments relied on analytical tools, visual, field and laboratory experiments for core samples collected from the building. The analytical checks of the building revealed considerable deflections of some slabs because of design error. The field and chemical analysis tests performed, confirmed the occurrence of durability defects as a result of poor workmanship during the construction stage. Several state-of-the-art repair techniques and materials were used for enhancing the service life of the structure at a minimum cost. The Repair strategy implemented included, removal of the deteriorated concrete, pouring a bonding agent on the surface of the damage, followed by injecting high strength cementitious grouts, supporting the deflected slabs using I-section steel beams, using cathodic protection to prevent corrosion, strengthening the columns and beams using carbon fiber reinforced polymer (CFRP) sheets, and steel jackets. Doi: 10.28991/cej-2020-03091630 Full Text: PDF